Grimm language : grammar, gender and genuineness in the fairy tales - Robinson, Orrin W., 1947- (Linguistic approaches to literature, 2010)
Addresses a number of issues in the Grimms' fairy tales from a (Germanic) linguist's point of view. Dealing with the Grimms' use of regional dialect material, various grammatical constructions, and specific nouns and adjectives in their "Children's and Household Tales", this book argues that the Grimms were following a number of objectives.